Successful Principal Leadership in Times of Change
VI, 205 p.
Keywords: The leadership of school principals is an enormously powerful influence on the quality of schools and the learning of pupils. While the work of principals has been examined intensively over the past 20 years, almost no effort has been made to understand the role from an international or cross-cultural perspective. This book contributes significantly to our understanding of successful school leaders by describing similarities and differences in the work of such leaders in countries ranging from England to Australia, the United States to Norway, Sweden to Hong Kong. Bringing together case study research, the book helps explain what all successful principals do and the ways in which context shapes some of their work. 'The research reported in the book present an interesting and rich picture of successful principals in different socio-cultural contexts and their reponses to national accountability policies. This book will make an important contribution to the existing body of knowledge about leadership practices.' Prof.dr. P. Sleegers, Faculty of Social- and Behavioural Sciences, University of Amsterdam, The Netherlands.